2006
DOI: 10.1253/circj.70.202
|View full text |Cite
|
Sign up to set email alerts
|

Four Cases of Kawasaki Syndrome Complicated With Myocarditis

Abstract: yocarditis frequently occurs in the acute phase of Kawasaki syndrome (KS) and may be transient, 1,2 but there are a few cases of severe myocarditis. [3][4][5][6][7][8] We present 4 cases of myocarditis in KS that required additional catecholamine treatment for severe left ventricular dysfunction (LVD).Case Reports (Table 1, Fig 1) Patient 1 (Fig 1A) A 7-year-old-girl (height 115 cm, body weight 20 kg) was admitted to a general hospital because of 4 days of persistent fever and right cervical adenopathy (white … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 12 publications
2
34
0
Order By: Relevance
“…The following are the common findings between our case and other patients with myocarditis 5,6) : 1) the patients with symptomatic myocarditis were older than 6 years, and 2) cervical lymphadenopathy and fever were the only initial features of KD.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The following are the common findings between our case and other patients with myocarditis 5,6) : 1) the patients with symptomatic myocarditis were older than 6 years, and 2) cervical lymphadenopathy and fever were the only initial features of KD.…”
Section: Discussionsupporting
confidence: 67%
“…In comparison, symptomatic myocarditis with congestive heart failure and inotropic treatment has been reported [5][6][7] . It is known that IVIG treatment reduced the prevalence of coronary disease and improved myocardial function in patients with KD to accompany myocarditis with clinical or subclinical left ventricular dysfunction 6,7) . Although IVIG therapy improved myocardial function, it may sometimes induce hypotension 8) .…”
Section: Discussionmentioning
confidence: 99%
“…Findings from the histological viewpoint have been diverse, and among these are found the following: hypertrophy; myocyte degeneration; fibrosis; infiltration of lymphocytes and plasma cells, and disarray of myocardial fibers and, in adults after KD, we find the description of kariomyocyte dropout and diffuse fibrosis not in the watershed distribution of the epicardial coronary arteries; it has been supposed that the fibrosis is due to ischemic damage because of microinfarcts or kariomyocyte inflammatory damage. Mycocarditis in KD is characterized by inflammatory cell infiltration from the coronary arteries to the myocardiac instersticium, and necrosis of the myocardium is infrequently observed (Yoshikawa, 2006); on the other hand, diffuse myocarditis followed by myocardial fibrosis can lead to diastolic dysfunction, and in the acute phase of KD, measurement of ventricular flow has revealed an abnormal relaxation and has been associated with increased levels of type B naturiuretic peptide. By other hand Myocarditis is recognized as a component on the half of KD patients, thought the left ventricular dysfunction ; Ajami, et al, evaluated myocardial function in patient during acute phase of illnees using the myocardial performance index also known as a Tei index, and they assessed the Tei index, the ejection fraction, shortening fraction and valvular regurgitation, pericardial effusion or coronary arterial involvement, they compared the changes in acute phase compared with pos-treatment data, confirming left ventricular dysfunction these index measures combined systolic and diastolic function is a simple sensitive and accurate tool for estimating myocardial function (Ajami 2010;Kurotobi, 2005).…”
Section: Myocarditismentioning
confidence: 99%
“…By these methods and by echocardiography, it has been observed that there is improvement in the myocarditis after treatment. This situation probably is related with the fact that myocarditis has been considered as a transitory event, without its being studied more profoundly (MacMorrow, 2001;Newburger, 2004;Yoshikawa, 2006).…”
Section: Echocardiographymentioning
confidence: 99%
“…I excluded 29 patients who received concomitant IVIG and anti-inflammatory therapy, four patients who had developed CAL before the start of therapy, and seven patients with disease recurrence and one patient who developed left ventricular dysfunction because of their greater prevalence of CAL [9,10,11].…”
mentioning
confidence: 99%